INFLUENCE OF SOCIAL MEDIA ON THE FOOD CHOICES AND EATING HABITS OF UNDERGRADUATES OF TECHNOLOGY AND VOCATIONAL EDUCATION STUDENTS IN NNAMDI AZIKIWE UNIVERSITY AWKA (NAU Journal of Technology and Vocational Education, 2026)
This study investigated the influence of social media on food choices and eating habits of undergraduates of Technology and Vocational Education (TVE), Nnamdi Azikiwe University, Awka. Specifically, it examined the influence social media platforms have on students, the role of social media in shaping dietary preferences, and the extent to which advertising and influencers influence students’ eating habits. The study adopted a descriptive survey design. Data was collected using a structured questionnaire and administered through Google Forms questionnaire. The questionnaire was validated and the reliability co-efficient of 0.89 was ascertained using Cronbach Alpha. Data were analyzed using mean and standard deviation. Findings revealed that social media significantly influences food choices by encouraging dietary experimentation, stimulating cravings through advertising, and promoting fast-food consumption. Influencers further shape students’ dietary decisions through recommendations and visual content. The study concludes that social media has profound effect on TVE undergraduates of Nnamdi Azikiwe University Awka eating habits both positively and negatively. The study recommended increased nutrition education, responsible advertising practices, and awareness campaigns that promote healthy eating among undergraduates.
Keywords: social media; food choice; eating habits; TVE undergraduates